(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
Developing an indigenous mold of scientific framework requires a conceptual formulation of an important term. It needs to be anchored in principle encompassing the philosophical, theoretical and methodological implications so that the term produced will become the basis of a research program. This paper aims to develop such a concept that is exclusive in Malay linguistics, which is proposed as reti bahasa. The analysis begins by debating reti bahasa according to Hassan Ahmad (2016), who uses the term tahu bahasa. The meaning of tahu bahasa is explained, and the reasons for replacing it with reti bahasa are also given. The term reti bahasa is then debated according to its etymological, historical and sociological perspectives to highlight its original meaning. Four main principles are coined from its original meaning, namely tatabahasa, tataberbahasa, tatalaku and tatafikir. Evidence of the existence of these four principles are subsequently linked to the works written by the indigenous scholars who not only described the linguistic system and structure of Malay linguistics, but also transcended the ‘perfection’ of the system and structure to ‘perfecting’ the personality of the speaker. The paper also asserts that the concept of reti bahasa is likely to prove the existence of an authentic Malay linguistic tradition. Full text: PDF